Migration Policy and its Interactions with Aid, Trade, and Foreign Direct Investment Policies A Background Paper - Xenogiani, Theodora (OECD Development Centre Working Papers, 2006)
It is recognised that migration can, under certain conditions, generate important net gains for the migrants' home countries. These gains may be in terms of growth, poverty reduction, insurance against risk and accumulation of human capital. Moreover migration may interact in various and complex ways with other policy vectors such as trade, investment and development assistance and they may have various joint impacts on development. This paper reviews the literature on the impact of migration on development. It also identifies the major methodological issues in terms of data use, data availability and econometric techniques. Moreover it investigates the joint development impact of migration, trade, investment and development assistance and assesses the degree of substitutability and/or complementarity among them. It shows that there is a great degree of heterogeneity of outcomes across countries and regions of the world and across time. The paper concludes by drawing some main lessons from the literature